Before She Disappeared a Novel - Gardner, Lisa ([New York] : Dutton, 2021)
Recovering alcoholic Frankie Elkin has devoted her life to searching for lost and forgotten missing persons. Frankie faces resistance from the police and the victim's family in the case of missing Haitian teen, Angelique Badeau.
A recovering alcoholic with more regrets than belongings, Frankie Elkin spends her life doing what no one else will-- searching for missing people the world has stopped looking for. A new case brings her to Mattapan, a Boston neighborhood with a rough reputation. She is searching for Angelique Badeau, a Haitian teenager who vanished from her high school months earlier. Resistance from the Boston PD and the victim's wary family tells Frankie she's on her own. She soon learns she's asking questions someone doesn't want answered. Now the next person to go missing could be her. -- adapted from jacket
108550
Keywords: Missing persons -- Fiction; Cold cases (Criminal investigation); Alcoholics; Thrillers; Boston (Mass.); Fiction